Pengaruh Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Kabupaten Badung, 1980-2009 - , I Made Endra Kartika Yudha, SE, Dr. Budiono Sri Handoko, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Abstract. This thesis aims to analyze the impact of government spending to economic growth before and after regional autonomy in the Badung regency period 1980 to 2009. Assessment results obtained by means of Error Correction Model (ECM) analysis that populared by Engle-Granger. The results of this study is the impact of government spending ( productive and unproductive spending) have a positive impact and significant to economic growth in the short term and long-term in Badung regency. Furthermore, regional autonomy does not lead to differences in the influence of government expenditure to economic growth in the short term and long-term in Badung regency.